2019
DOI: 10.4314/jae.v23i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Phone Applications by Farmers in North West Nigeria

Abstract: This study investigated extent of use of mobile phone applications among farmers in North-West Nigeria. A multi-stage sampling procedure was used to select 385 respondents for the study. Data were collected through the use of pre-tested structured questionnaire and summarized using frequency counts, percentages, mean and standard deviation. The Tobit regression model was used for inferential deductions. The results show that the majority (96%) owned a mobile phone; awareness of the call app and SMS app were100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
4
1
Order By: Relevance
“…The findings in Table 2 indicate that farmers' utilization of mobile phone indicate moderate response level of the majority on the communication channel to access knowledge on groundnut recommended practices that is quite commendable, considering the level of literacy of farmers' in the third world countries with its attendant consequences of inadequate infrastructure. However, the finding is contrary to the low usage identified by Abdullahi et al (2019) study that out of the 14 apps at disposal, only two (voice call and SMS apps) considered were prominently put to use by farmers in the North West Nigeria. Similarly, the findings in Table 3 reveal a moderate utilization level of individual extension method.…”
Section: Discussioncontrasting
confidence: 91%
“…The findings in Table 2 indicate that farmers' utilization of mobile phone indicate moderate response level of the majority on the communication channel to access knowledge on groundnut recommended practices that is quite commendable, considering the level of literacy of farmers' in the third world countries with its attendant consequences of inadequate infrastructure. However, the finding is contrary to the low usage identified by Abdullahi et al (2019) study that out of the 14 apps at disposal, only two (voice call and SMS apps) considered were prominently put to use by farmers in the North West Nigeria. Similarly, the findings in Table 3 reveal a moderate utilization level of individual extension method.…”
Section: Discussioncontrasting
confidence: 91%
“…The findings imply that farmers are not knowledgeable of the technical applications, especially those found within smartphones, because of their education. The findings are consistent with those ofUjakpa et al (2021) andAbdullahi et al (2019), who found that voice calls and SMS were the most prominent applications used for social and agricultural purposes. The findings underscore the fact that farmers' awareness level of mobile phone applications is generally low because they require functional literacy and technical competence.…”
supporting
confidence: 90%
“…Awareness and knowledge: Farmers' awareness and knowledge about the availability and benefits of smartphone apps in livestock farming play a crucial role. If farmers are aware of the apps' existence and understand how they can improve their farming practices, they are more likely to adopt and use them [25].…”
Section: Factors Influencing the Use Of Smartphones App In Livestock ...mentioning
confidence: 99%